Prevalence And Risk Factors Of Drug-induced Gingival Overgrowth In Hypertensive Patients - Haslina Taib; Muhammad Haziq Mohd Radzwan; Muhammad Annurdin Sabarudin; Wan Majdiah Wan Mohamad; Noraini Mohamad (Journal of Dentistry Indonesia, 2024)
Indexed by WOS